Research on the Application of Signal Integration Model in Real-Time Response to Social Events - Liu, Ziwei (Journal of Computer, Signal, and System Research, 2025)
With the increasing complexity of social events, how to quickly respond and make precise decisions in a dynamic and changing environment has become a key issue in the field of public management. The signal integration model, as an advanced information fusion technology, greatly improves the timeliness of event responses and the quality of decision-making by summarizing information from various data sources. This article deeply analyzes the application of signal integration models in handling social events, and explores the specific roles of the models in information collection, data synthesis, real-time response, and decision assistance. In the practical application stage, this article focuses on how to apply the signal integration model in social events, including how to integrate diverse signal sources, establish a rapid response system, and optimize decision-making processes. Through empirical analyses on multiple instances, the signal integration mode has been evaluated in terms of response speed, decision assistance effectiveness, and practical operational feedback. Research has suggested that the signal integration mode not only significantly improves the efficiency of responding to social events, but also enhances the accuracy of decision-making, providing solid technological support and theoretical basis for handling similar events in the future.